Intransitive Independent Clauses in Film â€œá¸ŽÄ«bâ€: Modern Linguistic Study Based on Kenneth L. Pikeâ€™s Tagmemic Perspective - Basid, Abdul; Syahril, Muhamad; Muzakky, Mohamad Irvan; Muttaqin, Ichwanul; Imaduddin, M. Firdaus; Masrokhin, Masrokhin (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This study aimed to reveal the structures of intransitive independent clauses in the film â€œá¸ŽÄ«bâ€ based on the perspective of Kenneth L. Pikeâ€™s tagmemic theory. This was a qualitative descriptive study. This study gathered data from an Arabic film entitled á¸ŽÄ«b directed by Naji Abu Nowar. The data collection techniques used in this study were watching, translating, and note-taking techniques. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicated that there were four structures of intransitive independent clauses in the film â€œá¸ŽÄ«b,â€ namely: (1) S + P consisted of three parts: The first was S + P. The second was the intransitive independent clause = NP + IVP. The third covered slot containing S + P, class which entailed NP + IVP, role that subsumed S + P, and cohesion without objects. (2) P + S + Adjunct (Adj â€“ NP) comprised three parts. The first was P + S + Adj â€“ NP. The second was the intransitive independent clause = IVP + NP1 + NP2. The third consisted of slot which contained P + S + Adj, class that subsumed IVP + NP1 + NP2, role which entailed P + S + Adj, and cohesion without objects. (3) P + S + Adjunct (Adj â€“ PP) had three parts. The first was P + S + Adj â€“ PP. The second was the intransitive independent clause = IVP + NP + PP. The third involved slot which entailed P + S + Adj, class that subsumed IVP + NP + PP, role comprised of P + S + Adj, and cohesion without objects. (4) S + P + Adjunct (Adj â€“ AP) consisted of three parts. The first was S + P + Adj â€“ AP. The second was the intransitive independent clause = NP + IVP + AP. The third comprised slot containing S + P + Adj, class which subsumed NP + IVP + AP, role consisting of S + P + Adj, and cohesion without objects.